The impact of monetary policy in attracting foreign investment in light of the economic reform policy kurdistan region of iraq as a model - Hatim, Raysan; Al-Khazraji, Thuraya (Humanities Journal of University of Zakho, 2023)
The importance of foreign investment in the economies of all countries emerges as a form of alternative financing to foreign loans or indebtedness. Therefore, countries seek to grant facilities and incentives and create an appropriate climate in order to attract foreign investment to them. Developing countries, in particular, want to catch up with the path of development and achieve development, and are working seriously to attract foreign investment and employ it in economic development projects. As for monetary policy, it is one of the important determinants of foreign direct investment, through its included indicators (exchange rates, interest rates, inflation) because each of these indicators has a fundamental role in stimulating the economy to move towards the flow of foreign investment. We find that the exchange rate is one of the most important policy variables. Economic openness and its impact on the overall economy (trade, capital flows, foreign investment, global reserves, remittances). As for the inflation rate, it represents an indicator of the stability of the local economy, and that changes in inflation rates affect the investment decision and have a negative impact on attracting foreign investment. As for interest rates, their rise in the country will attract foreign investors. As for the Kurdistan Region, we find that there is a will and a vision to attract foreign direct investment and work to create appropriate conditions and necessary requirements that will contribute to the flow of foreign investment and capital to the region. In addition, the desire of the economy in Iraq in general and in the region in particular coincided with the application of the principle of economic reform and structural adjustment as one of the prescriptions of international institutions such as the International Monetary Fund (IMF) and the World Bank (IB) for the purpose of achieving high rates of growth in developing countries and creating a suitable climate for applying the principle of the market mechanism and exit. From the principle of centralization in economics. Practically, the economic reform processes began after 2003, and they helped to some extent open the doors in the economy of the region, especially for the influx of foreign direct investment, which contributed to some extent in obtaining remarkable economic growth rates with the desire of decision-makers in the Kurdistan Region to achieve higher growth rates that lead to more of economic development and development in the region.